Lacan and Klein : creation and discovery : an essay of reintroduction - Rosen-Carole, Adam, 1979- (Lexington Books, 2011)
This book reconstructs the metapsychological and clinical theories of Melanie Klein and Jacques Lacan in a manner designed to redress prevalent mischaracterizations of their works that are largely responsible for the deadlocked polemics between partisans of Kleinian and Lacanian camps.